Design of a Prototype of Water Purification by Plasma Technology as the Foundation for an Industrial Wastewater Plant. - Barillas-Mora, Laura (Institute of Physics Publishing, 2015)
In order to mitigate the contamination of water sources due to the spill of sewage without any kind of treatment, mainly generated by the industrial sector; a prototype of water purification by plasma technology has been designed. The prototype will transform liquid water into plasma to eliminate the pathogens from the water, due to their exposure to ultraviolet radiation, electric fields and shock waves, which aid in the destruction of pollutants. The sewage will be accelerated at high speed to convert it into a liquid-gas mixture in order to transform it into plasma, which is achieved when the electrical discharge (of the type dielectric barrier discharge or DBD) is applied to the water by means of high voltage electrodes, from a source of alternating current (AC). Subsequently, the mixture slows down to be return into liquid phase and obtain clean water, all of these without a significantly rise of temperature. The device also has an automatic power control system. Finally, a short feasibility study was conducted in order to use this type of water cleaner in the future as a basis for a treatment plant of industrial waste water, so it comes to replace the current secondary and tertiary treatments used among the industry. It is intended that this new system will be more efficient and cheaper than the current waste water treatments. © Published under licence by IOP Publishing Ltd.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938099563&partnerID=40&md5=c53190f5ec3d59b3c1bee87e74b2f904
Keywords: Dieléctricos; Gases licuados; Líquidos; Aguas residuales; Descargas eléctricas; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering